2013
DOI: 10.3324/haematol.2013.084434
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Polo-like kinase 1 causes growth reduction and apoptosis in pediatric acute lymphoblastic leukemia cells

Abstract: This study investigated Polo-like kinase 1, a mitotic regulator often over-expressed in solid tumors and adult hematopoietic malignancies, as a potential new target in the treatment of pediatric acute lymphoblastic leukemia. Polo-like kinase 1 protein and Thr210 phosphorylation levels were higher in pediatric acute lymphoblastic leukemia (n=172) than in normal bone marrow mononuclear cells (n=10) (P<0.0001). High Polo-like kinase 1 protein phosphorylation, but not expression, was associated with a lower probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…9 As far as malignant blood disorders are concerned, PLK1 is expressed at high levels in chronic myelogenous leukemia (CML), 10 acute myelogenous leukemia (AML), 11 and acute lymphoblastic leukemia (ALL). 12 Overexpression of AK-A and -B has polo-like kinases (pLKs) and Aurora kinases (AKs) act as key cell cycle regulators in healthy human cells. In cancer, these protein kinases are often overexpressed and dysregulated, thus contributing to uncontrolled cell proliferation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…9 As far as malignant blood disorders are concerned, PLK1 is expressed at high levels in chronic myelogenous leukemia (CML), 10 acute myelogenous leukemia (AML), 11 and acute lymphoblastic leukemia (ALL). 12 Overexpression of AK-A and -B has polo-like kinases (pLKs) and Aurora kinases (AKs) act as key cell cycle regulators in healthy human cells. In cancer, these protein kinases are often overexpressed and dysregulated, thus contributing to uncontrolled cell proliferation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in addition to inhibition of cell proliferation, pancreas cancer cell transfected with mir3686 demonstrated enhanced apoptosis. Several reports had documented that inhibition of PLK1 in variety cancer cell lines could result in growth reduction and induce apoptosis [ 27 , 28 ]; however, the detailed mechanism of how PLK1 interaction with the cellular apoptosis pathway is still known and needs further investigation. In addition to a previous report that demonstrated that overexpression of PLK1 had been observed in the early stage of pancreas cancer, our data suggested that PLK1 might be a promising target for the treatment of pancreas cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of pediatric acute lymphoblastic leukemia (ALL) samples were evaluated for Plk1 expression and responsiveness to NMS‐P937. Compared to normal bone marrow controls, pediatric ALL had higher Plk1 expression and was more sensitive to inhibition with NMS‐P937 . Other studies have shown its anti‐proliferative effects in a wide array of solid tumor and hematologic malignancies cell lines .…”
Section: Nms‐p937 (Nms‐1286937) (Nerviano Medical Sciences)mentioning
confidence: 90%